A survey of inconsistency indices for pairwise comparisons. Issue 8 (17th November 2018) - Brunelli, Matteo
ABSTRACT: Pairwise comparisons are a well-established tool to compare weights of criteria and alternatives or, more in general, any entities. Their ultimate goal is to facilitate the search for a suitable weight vector. In this context, the concepts of inconsistency and inconsistency index have emerged. This manuscript has two goals. Firstly, it surveys the most relevant inconsistency indices by means of a self-contained exposition. Secondly, by analyzing recent trends and milestones it presents some conclusions and a discussion on possible directions of future research.